The use of zootherapeutics in folk veterinary medicine in the district of Cubati, Paraíba State, Brazil - da S Mourão José; de MS Souto Wedson; Barboza Raynner RD (BMC, 2007)
Abstract Background The present work addresses the use of zootherapy in folk veterinary medicine (ethnoveterinary) by the residents of the municipal district of Cubati, microregion of Seridó, Paraíba State, Brazil. It sought to identify the principal animals used as medicinal sources for zootherapeutics and to contribute to the preservation and sustainability of this traditional knowledge. Methods Field research was undertaken on a weekly or biweekly basis during the period November, 2006, to January, 2007. Free, semi-structured, and open interviews were made with local residents of the municipal district of Cubati (in both urban and rural settings) as well as with venders in public markets. A total of 25 individuals of both sexes were interviewed (with ages varying from 26 to 78 years) although only 16 were finally chosen as informants as these people demonstrated the greatest degree of knowledge concerning zootherapeutics. Graphs and percentages were generated using Microsoft© Excel 2007 software, and the species were identified by photographic registration and subsequent bibliographical surveys. Results Mammals constitute the main medicinal zootherapeutic source for folk veterinary medicines in the studied area, both in terms of the total number of species used and the frequency of their citation. Sheep (Ovis aries), pigs (Sus scrofa), cattle (Bos taurus), and foxes (Cerdocyon thous) were mentioned by 62.5, 43.75, 37.5, and 31.25% of the informants, respectively, as being used in folk veterinary medicine. Additionally, chameleons (Iguana iguana), chickens (Gallus domesticus), and rattlesnakes (Crotalus durissus) were mentioned by 75, 43.75, and 31.25% of the informants, respectively. Relatively simple animal illnesses, such as furuncles, or injuries resulting from embedded thorns or skin eruptions are responsible for the largest number of zootherapeutic treatment, while, diseases of greater complexity, such as rabies and brucellosis, were not even mentioned. Fat from various animals constituted the most frequently cited resource used for its medicinal-veterinary properties. Conclusion The examination of folk knowledge and health practices allows a better understanding of human interactions with their local environment, and aids in the formulation of appropriate strategies for natural resource conservation.